Assessing Adherence to Responsible Reporting of Suicide Guidelines in the Canadian News Media: A 1-year Examination of Day-to-day Suicide Coverage: Évaluer la conformité au journalisme responsable en matière de directives sur le suicide dans les médias canadiens d'information: Un examen d'une année de la couverture quotidienne du suicide. (September 2020) - Antebi, Lara; Carmichael, Victoria; Whitley, Rob
Objective: This study aims to examine routine day-to-day suicide reporting in the Canadian media, giving a descriptive overview of the tone and content of news articles. The primary objective is to assess adherence to responsible reporting of suicide recommendations in news articles about suicide. A secondary objective is to categorize these articles according to their focus. A tertiary objective is to compare guideline adherence across the different categories of articles. Methods: We collected news articles containing the keyword "suicide" from 47 Canadian news sources between April 1, 2019, and March 31, 2020. Articles were read and coded for their adherence to responsible reporting of suicide recommendations. Articles were also allotted into categories according to their focus and primary suicide discussed. Frequency counts and percentages of adherence were calculated for all key variables—both overall and by category of article. Chi-square tests were also conducted to assess for variations in adherence by category of article. Results: The procedures resulted in 1, 330 coded articles. On the one hand, there was high overall adherence to several recommendations. For example, over 80% of articles did not give a monocausal explanation, glamourize the death, appear on the front page, include sensational language, or use discouraged words. On the other hand, there was low adherence to other recommendations, especially those related to putatively protective content. For example, less than 25% included help-seeking information, quoted an expert, or included educational content. Cross-category analysis indicated that articles about events/policies/research and Indigenous people had the highest proportions of adherence, while articles about murder-suicide and high-profile suicides had the lowest adherence. Conclusions: While a substantial proportion of articles generally adhere to suicide reporting recommendations, several guidelines are frequently underapplied, especially those concerning putatively helpful content. This indicates room for improvement in the responsible reporting of suicide.